LinkedIn as a Strategic Brand‑Building Tool: A Dual Perspective on Personal and Corporate Branding - Degjoni,Aldiron; Klinga,Marcus; Ortega,Gregorio (LBMG Strategic Brand Management - Masters Paper Series, 2025)
Purpose: To study how LinkedIn can be used as a strategic brand-building tool across two dimensions: 1) for individual professionals and 2) for organizations. The study explores the relationship between brand identity and audience engagement, and how it can be leveraged in digital branding. Methodology: A qualitative case study across the two dimensions. We use secondary data and abductive reasoning to form an understanding of how LinkedIn can be leveraged for branding, iteratively combining insights from the empirical cases with applied theories. Findings: The paper introduces two conceptual frameworks, offering a diagnostic tool to evaluate branding effectiveness on LinkedIn. It also suggests updated interpretations for digital engagement and identity, fitting traditional branding theories to the LinkedIn context. Research Limitations: The study by a limited sample size and reliance on publicly observable data, as well as its focus on high-profile Western cases. Further research should be conducted on broader demographics and platform-specific algorithmic dynamics. Practical Contributions: We present two matrices providing actionable frameworks for organizations and professionals aiming to improve their branding on LinkedIn. By mapping their positioning, users can gain strategic insights and support to guide their branding efforts. Originality: This paper is the first known to synthesize classical brand identity theory with platform-specific dynamics of LinkedIn, using the dual perspective of both organizations and individuals. Keywords: LinkedIn, Brand Identity, Digital Branding, Brand Engagement, Patagonia, IKEA, Tony Robbins, Nicolai Tangen Paper Type: Research Paper
Keywords: LinkedIn; Brand Identity; Digital Branding; Brand Engagement; Patagonia; IKEA; Tony Robbins; Nicolai Tangen